PERAN HAMBA TUHAN DALAM MEMPROMOSIKAN MODERASI BERAGAMA: PERSPEKTIF KEAGAMAAN - Delvita Mery Katrin; Yoran Pali' Padang, Christy Sarajar, Marce Norlina Ton (ADISAM PUBLISHER, 2025)
Religious conflicts in Indonesia a difficult challange in building in the integrity and unity of the nation’s insight. Amid rising polarization of religious identities and the spread of radicalism in various forms, religious moderation has become a strategic approach to maintaining social harmony and religious freedom in pluralistic societies. This study aims to analyze the role of religious leaders in promoting the values of religious moderation from a Christian theological perspective. Using a descriptive qualitative method and literature review, this article examines how values such as love, tolerance, and justice taught in the Bible serve as ethical foundations for cultivating a balanced religious attitude. Religious leaders function not only as spiritual guides but also as agents of social transformation and mediators between different faith communities. This study finds that the strategic role of religious leaders includes teaching moderation through preaching and education, facilitating interfaith dialogue, and exemplifying moderation in public life. It suggests the need for strengthening the theological and social capacities of religious leaders so they can actively contribute to peacebuilding and prevent religion-based radicalism